Cooperation Structures - Premises of Economic Reindustrialization and Regionalization - Beudean, Ioan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Romanian enterprises are looking for solutions to reduce the technological gap compared to the West of Europe,to increase competitiveness and their creative potential. Only a small fraction of them have the chance to be integrated into government programs complementary to their work, facilitating their progress. This publication describes some possible practical ways from which enterprises can gain access to the advanced research results and to technological potential of other evolved units through cooperative actions. The ideas and conclusions of our work can be useful both for economical entities management and also to institutions who develop national economic programs, as facilitating cooperation is a goal almost absent from these concerns.